Deregulation of Cancer-Associated Genes in Odontogenic Cysts - İbrahim Bozgeyik; Önder Yumrutaş; Bilal Ege (Cumhuriyet University, 2019)
Objectives: The aim of the present study was to demonstrate the key role of differential expression levels of RB1, TP53, XIAP, BCL2 AIFM3, BAX, CASP3 and CASP9 genes in odontogenic cysts. Materials and Methods: A total number of 15 patients who diagnosed with odontogenic cyst were enrolled for the present study. For the quantitative gene expression analysis, cyst and adjacent gingival healthy tissues of patients were collected during surgical assessments. Quantitative analysis of gene expression levels RB1, TP53, XIAP, BCL2 AIFM3, BAX, CASP3 and CASP9 were achieved real-time PCR method. For the optimization of gene expression levels GAPDH reference gene was used. Results: Expression of both RB1 and TP53 genes were markedly diminished in odontogenic cysts tissues as compared to healthy tissues (p<0.05). Likewise, levels of CASP3 and CASP9 genes were found to be significantly reduced in odontogenic cysts tissues compared to healthy tissues (p<0.05). In contrast, expression levels of XIAP was significantly elevated (p<0.05). Although BCL2, AIFM3, and BAX genes were also differentially expressed in odontogenic cysts tissues, these variations were statistically insignificant (p>0.05).  Conclusions: The findings of the present study indicates that RB1, TP53, XIAP, CASP3 and CASP9 genes might have chief roles in formation odontogenic cysts and responsible for the increased cell proliferation in these tissues.